2005
DOI: 10.1677/joe.1.05948
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic overexpression of neuromedin U promotes leanness and hypophagia in mice

Abstract: Recent work has shown that neuromedin U (NmU), a peptide initially identified as a smooth muscle contractor, may play a role in regulating food intake and energy homeostasis. To further evaluate this putative function, we measured food intake, body weight, energy expenditure and glucose homeostasis in transgenic mice that ubiquitously overexpress murine proNmU. NmU transgenic mice were lighter and had less somatic and liver fat, were hypophagic, and had improved insulin sensitivity as judged by an intraperiton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 60 publications
3
52
1
1
Order By: Relevance
“…We found that increased NMU in the xenograft tumors were associated with cancer cachexia in mice. NMU itself has an anorexigenic effect in animals (Howard et al, 2000;Hanada et al, 2004;Shousha et al, 2006), and transgenic overexpression of it promotes leanness in mice (Kowalski et al, 2005). As NMU can function as a proinflammatory mediator by promoting interleukin (IL)-6 production in Th2-type T cells or macrophages (Johnson et al, 2004;Moriyama et al, 2006) and inhibition of IL-6 can partially attenuate or reverse cancer cachexia (Strassmann and Kambayashi, 1995), this might be a mechanism underlying NMU-mediated cancer cachexia.…”
Section: Discussionmentioning
confidence: 99%
“…We found that increased NMU in the xenograft tumors were associated with cancer cachexia in mice. NMU itself has an anorexigenic effect in animals (Howard et al, 2000;Hanada et al, 2004;Shousha et al, 2006), and transgenic overexpression of it promotes leanness in mice (Kowalski et al, 2005). As NMU can function as a proinflammatory mediator by promoting interleukin (IL)-6 production in Th2-type T cells or macrophages (Johnson et al, 2004;Moriyama et al, 2006) and inhibition of IL-6 can partially attenuate or reverse cancer cachexia (Strassmann and Kambayashi, 1995), this might be a mechanism underlying NMU-mediated cancer cachexia.…”
Section: Discussionmentioning
confidence: 99%
“…injection of NMU gives a clear catabolic response, increasing core body temperature and locomotor activity, reducing food intake (Nakazato et al 2000) and acute administration of NMU into the PVN has clear anorexigenic effects (Wren et al 2002); however, chronic injections of NMU into the PVN have no effect on food intake or body weight. Nevertheless, the NMU knockout mouse shows clear hyperphagia and obesity ) and the transgenic mouse overexpressing NMU is lean and hypophagic (Kowalski et al 2005). Recently, it has been demonstrated that at least some of the effects of leptin are mediated via NMU (Jethwa et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It is also involved in the regulation of circadian rhythmicity (Nakahara et al 2004) and luteinizing hormone secretion (Quan et al 2003). The NMU knockout mouse is hyperphagic and obese , while the transgenic mouse, overexpressing NMU, is lean and hypophagic (Kowalski et al 2005) providing strong support for the role of NMU in energy balance.…”
Section: Introductionmentioning
confidence: 99%
“…These mice also develop late-onset hyperglycemia and hyperlipidemia [75]. Transgenic mice that overexpress NMU are hypophagic, and have reduced body weight, low somatic and liver fat, and improved insulin sensitivity [76]. On a high fat diet, these mice remain lighter than wild types and eat less [76].…”
Section: Neuromedin Umentioning
confidence: 99%
“…Transgenic mice that overexpress NMU are hypophagic, and have reduced body weight, low somatic and liver fat, and improved insulin sensitivity [76]. On a high fat diet, these mice remain lighter than wild types and eat less [76]. A variant in the human NMU gene has also been linked to obesity in the human population [77].…”
Section: Neuromedin Umentioning
confidence: 99%